The Function and Role of Chinese Language in the Import Business of Goods at PT Anson Ratu Bakindo - Johan, Johan; Annie, Annie; Fawnia, Pretty; Ivana, Ivana; Jessy, Jessy (Jurnal Indonesia Sosial Sains, 2025)
Mandarin is currently significant in global commerce, particularly in the import sector, where it involves collaboration with Chinese trading partners. As one of the world’s leading exporters, proficiency in Mandarin is a key advantage for businesses aiming to broaden their market presence and ensure efficient import operations. This research aims to thoroughly examine how the function and role of the Mandarin language are utilized in the operational aspects of PT Anson Ratu Bakindo, including communication and negotiation processes, document management, and the maintenance of business relationships with Chinese suppliers. Through interviews and observations with the owner and employees at PT Anson Ratu Bakindo, it was found that the use of Mandarin directly enhances communication effectiveness, reduces language misunderstandings, and accelerates transaction processes. The results of this study indicate that if the company’s owner and purchasing department staff at PT Anson Ratu Bakindo possess fluent Mandarin language skills, daily operations can be conducted effectively without misunderstandings, such as incorrect types or quantities of delivered goods. Therefore, Mandarin language training for employees at PT Anson Ratu Bakindo, as well as recruiting staff with Mandarin proficiency, is recommended as part of the human resources development strategy and international business expansion. In conclusion, the Mandarin language not only serves as a medium of communication but also as a supporting factor for success in the import business.